Effect of active solar heating system on microclimate, development, yield and fruit quality in greenhouse tomato production. (March 2021) - Bazgaou, A.; Fatnassi, H.; Bouharroud, R.; Ezzaeri, K.; Gourdo, L.; Wifaya, A.; Demrati, H.; Elame, F.; Carreño-Ortega, Á.; Bekkaoui, A.; Aharoune, A.; Bouirden, L.
Abstract: Heating greenhouses is essential to provide favorable climatic conditions for growing plants under cold periods. In this article, we have studied the performance of an Active Solar Heating System (ASHS) consisting of two solar water heaters equipped with flat solar collectors, two storage tanks and exchanger pipes. During the day, the water is heated in the thermosyphon solar collectors and stored in tanks before being placed into circulation in the exchanger pipes to distribute the heat to the aerial and root zones of plants. To assess the performance of the Active Solar Heating System, climatic and agronomic parameters were monitored in two identical canarian greenhouses, one equipped with ASHS heater and the second without. Experimental results show that the ASHS system improve the nocturnal climatic conditions under greenhouse. The thermal comfort created by the ASHS system in root zone, increases the absorption of nutrients, which improve the external quality (color, size, weight and firmness) and the internal quality (sugar content, acidity and taste) of tomato fruits. This improvement is also reflected by increasing total tomato yield by 55% in winter period. The results of economic analysis indicate that the ASHS system is a cost effective in terms of investment and energy saving. Highlights: The Active Solar Heating System (ASHS) is proposed to heat a canarian greenhouse. This system creates a thermal comfort of tomato crop during the winter period. This system increases the absorption of essential nutrients, which improve external/internal quality of tomato fruits. The integration of ASHS in greenhouse applications is very profitable and could generate profits for farmers.